Determinants of external debt in Malaysia / Rina Zulaikha Zulkefli - Zulkefli, Rina Zulaikha (Faculty of Business and Management, 2019)
This paper examined on the factors of external debt with the variables of corruption, interest payments and military expenditure in Malaysia. This paper involved in a time series data which include solely one Asian country that is Malaysia for the period of 2007 until 2016 in a quarterly data. Secondary sources of data for all variables have been used and utilized data are extracted from the Transparency International and World Bank while the data were analyzed using EViews10’s through Descriptive Statistics test, Ordinary Least Square (OLS) regression model, Diagnostic Test and Stationary test. Based on the final results, among all the variables the study concluded, there is only one variable that is significant to the dependent variable which is the lag variable of external debt whilst other variables such as corruption, interest payments and military expenditure did not give any significant impact towards external debt.